Conversations with tradition: faith-based community development through the Eden Network in Cape Town - Kirkby, Heather (School of Architecture, Planning and Geomatics, 2018)
Community development is a tool in urban planning that, when used in contexts in the global South, can be used to perpetuate forms of "worlding" (Roy, 2011). "Worlding" tracks the way that urban models travel in asymmetrical ways from the global North to the global South. Christian Faith-Based Organisations (FBOs), in particular, are sites where this type planning is done. The perpetuation of asymmetries between the global North and the global South lies, partially, in Christianity's connection to iterations of urban citizenship. In the contemporary era, faith-based community development inhabits an ambivalent space, where it draws on Enlightenment traditions to legitimate action, while also invoking hope and conviviality in everyday local settings. I investigate the work that FBOs do in community development through a case study of the Eden Project in Salt River, Cape Town. I use a combination of desktop research, unobtrusive observation and interview, which I analyse using discourse analysis. I also review literature related to FBO community development. Through a thorough review of the literature on FBOs, I establish a set of assessment criteria by which I assess the case study. In the course of this research, I find that the Eden Network SA is an assemblage, which draws on global forms, or principles. These forms are assemblages because they adapt to the heterogeneous conditions of local areas. The Eden Network SA reiterates a version of "worlding", while also subverting parochialisms. The Eden Network SA invokes hope in its capacity to hold the tension between systemic concerns, while also acting on possibilities in particularised settings. These possibilities frequently relate to welfare functions, which means that this network plays a governance function in the local area it locates in. I suggest that FBOs are well-positioned for relational community development work. However, this work should be done in receptive, respectful ways that seek to join the daily life of the neighbourhood. This is the case because relationship-building is the primary foundation for participating in the life of an area. This requires a move away from goal-, or programme-led efforts to undertake community development, in favour of being in relationship with people, on their own terms.